Alliance Knowledge Sharing Unit: Strategy Overview 2025–2028 - Bailey, Arwen; Gichia, Timothy; Mobasher, Mahin (2025)
As a research organization, knowledge is the core of the Alliance’s business. Knowledge as formal evidence created through research, but also knowledge about the research process itself, methods, tools, and soft skills that support the process. Much of that knowledge is tacit, residing within researchers’ heads, or informal, scattered among reports and products across the Alliance. Knowledge sharing is about how we leverage that knowledge, connecting and aggregating it, engaging scientists to generate new ideas through conversations, and supporting processes so that potential users can add to their own knowledge through engagement with our research and researchers.